2017
DOI: 10.3892/ol.2017.5778
|View full text |Cite
|
Sign up to set email alerts
|

miR-185-3p regulates the invasion and metastasis of nasopharyngeal carcinoma by targeting WNT2B in vitro

Abstract: MicroRNAs (miRs) have been recognised as important regulators of malignant behaviour in different types of human cancer, including nasopharyngeal carcinoma (NPC). A previous study by our group revealed that miR-185-3p regulates the radioresistance of NPC cells. The present study aimed to investigate the effect of miR-185-3p on NPC invasion and metastasis. Human NPC CNE-2 and 5-8F cell lines were transfected with a miR-185-3p mimic and miR-185-3p inhibitor, respectively, and their effects on the invasion and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…**P < 0.01; ***P < 0.001. miR-504 is up-regulated in NPC radio-resistant cells and could directly down-regulated the expression of NRF1 and regulated mitochondrial-mediated oxidative responses, allowing NPC cells to gain radio-resistant characteristics [14]. miR-185-3p and miR-205 are also found to correlate with NPC radioresistance [15,16]. In the present study, we found miR-206 was downregulated in radioresistant NPC cells.…”
Section: Discussionsupporting
confidence: 58%
“…**P < 0.01; ***P < 0.001. miR-504 is up-regulated in NPC radio-resistant cells and could directly down-regulated the expression of NRF1 and regulated mitochondrial-mediated oxidative responses, allowing NPC cells to gain radio-resistant characteristics [14]. miR-185-3p and miR-205 are also found to correlate with NPC radioresistance [15,16]. In the present study, we found miR-206 was downregulated in radioresistant NPC cells.…”
Section: Discussionsupporting
confidence: 58%
“…Kallifatidis et al recently reported increased ARRB1 expression in bladder cancer cells, and ARRB1 gene knockout reversed the aggressive phenotype of bladder cancer cell lines [37]. MiR-185-3p is a potential oncosuppressor miRNA evident in nasopharyngeal carcinoma (NPC), and the inhibition of miR-185-3p promoted invasion and metastasis of NPC cells [38]. In the current study, altered miR-185-3p-ARRB1 interaction was identified in EGCG-treated bladder TCC cells, with 3.92-fold up-regulated miR-185-3p and 4.01-fold suppressed ARRB1.…”
Section: Discussionmentioning
confidence: 99%
“…After irradiation, the cells were cultured for another 12‐14 days and the number of surviving colonies (defined as a colony with > 50 cells) was counted. The survival fraction was calculated as we previously described . Each experiment was performed in duplicate or triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The survival fraction was calculated as we previously described. 14,17 Each experiment was performed in duplicate or triplicate.…”
Section: Plate Clonogenic Survival Assaysmentioning
confidence: 99%